Management of unilateral impacted maxilarry canine - I.B Adhiana, - (USU Press, 2017)
Background: The maxilarry canine plays a vital role in the functional aspect of the occlusion. They support lip, facial muscles, promote facial esthetics and important guideline in occlusion. An impacted canine is a canine that is prevented from erupting into its normal functional position by bone, tooth or fibrous tissue. The cause of canine impaction can be the result of localized, systemic or genetic factor. The diagnosis and localization of the impacted canine is the most important step in the management of impacted canine based on clinical and radiographic examinations.Intradisciplinary management is essential when the canines of orthodontic patients have failed to erupt on time. Treatment involves surgical exposure of the impacted tooth. Objective: The purpose of this treatment is correct the moderate crowding of anterior upper and lower arch, then making space for impacted canine after surgical approach. Case management: 21 years old Indonesian male with moderate anterior crowding. The clinical and radiographic examination showed skeletal Class I with Angle’s Class I malocclusion, moderate anterior crowding, unilateral impacted upper canine, increased overbite, straight profile. After levelling and aligning and maintain space for impacted canine, under active orthodontic treatment was referred from the Dept. of Orthodontics to Dept. of Periodontics Airlangga University. Result: Normal overjet and overbite with a Class I molar relationship were achieved. The upper canine were aligned in their correct position in the arch. Conclusion: The management of impacted canines is important in terms of esthetics and function and requires a qualified experience of a number of clinicians. Accurate localization, concervative management of soft tissues, selection of appropriate surgical approach, rigid anchorage unit, and the direction of the orthodontic traction are the important factors for the successful management of impacted canines.